2014
DOI: 10.1002/bdra.23285
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation aberrations rather than polymorphisms of FZD3 gene increase the risk of spina bifida in a high‐risk region for neural tube defects

Abstract: The results of this study suggest that DNA methylation plays an important role in FZD3 gene expression regulation and may be associated with an increased risk of spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…35 Aberrant methylation of the FZD3 gene, a PCP component, was observed in brain tissue in human spina bifida and showed an association with human NTD development. 12 Our findings expand the knowledge of the relation between these pathways and NTD development.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…35 Aberrant methylation of the FZD3 gene, a PCP component, was observed in brain tissue in human spina bifida and showed an association with human NTD development. 12 Our findings expand the knowledge of the relation between these pathways and NTD development.…”
Section: Discussionsupporting
confidence: 67%
“…Besides vague effect of global DNA methylation, disruption of methylation at specific genes has been linked to NTDs, such as imprinted genes, 9,10 transposon genes, 7 DNA repair genes, 11 planar-cell polarity genes, 12 folate receptor genes, 13 and HOX genes. 14 Hypermethylation or hypomethylation of these specific genes was identified in NTD cases by targeted gene methylation profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that global DNA hypomethylation, evaluated using LINE-1 methylation as an indicator in human fetuses, was associated with an increased risk for NTDs [9]. Aberrations of methylation at specific genes are reported to be involved in NTDs, including imprinted genes [10, 11], DNA repair genes [12], planar-cell polarity genes [13, 14], and HOX genes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Research from countries without FA fortification also lends support to the methylation hypothesis. A slight reduction in genome-wide DNAm was noted in NTD cases in China [ 14 16 ], in addition to changes in NTD DNAm at specific genes relevant to fetal development in China, Belgium, and the Netherlands: imprinted [ 17 ], planar-cell polarity [ 18 , 19 ], HOX [ 20 ], and folate receptor genes [ 21 ]. Some of the findings are, however, undermined by small magnitude of change in DNAm, a lack of statistical correction for multiple comparisons, and use of peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%